2018
DOI: 10.15406/ipcb.2018.04.00122
|View full text |Cite
|
Sign up to set email alerts
|

Malaria and anemia among pregnant women living in communities along the coast of Lagos Lagoon, South-west Nigeria

Abstract: Background: Malaria parasitemia during pregnancy is a most important public health problem to governments and to individuals in malaria endemic regions of the world. Moderate or severe anemia during pregnancy may be associated with heavy parasitic infestation. However, malaria may not be the only cause of anemia in pregnant women in developing countries. Objective: To determine the prevalence of malaria and anemia in different trimester, gravida and age group Study design: A cross-sectional study that recruite… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 24 publications
1
4
2
Order By: Relevance
“…These authors stated that P. falciparum was directly linked with maternal death in a low transmission setting while in a high transmission setting, it was an indirect cause of mortality through maternal anaemia. The prevalence of anaemia among pregnant women, in this study, was also found to be highest in the second trimester with prevalence of 45.31%, unlike that reported by Olukosi and Afolabi (2018) in Lagos in which their study revealed first trimester having a low prevalence of 27.5%. but with a higher prevalence of anaemia (84.1%).…”
Section: Discussioncontrasting
confidence: 82%
See 2 more Smart Citations
“…These authors stated that P. falciparum was directly linked with maternal death in a low transmission setting while in a high transmission setting, it was an indirect cause of mortality through maternal anaemia. The prevalence of anaemia among pregnant women, in this study, was also found to be highest in the second trimester with prevalence of 45.31%, unlike that reported by Olukosi and Afolabi (2018) in Lagos in which their study revealed first trimester having a low prevalence of 27.5%. but with a higher prevalence of anaemia (84.1%).…”
Section: Discussioncontrasting
confidence: 82%
“…The prevalence of anaemia in the present study was 44.0%, This agrees with a study conducted by Obi (2021) who reported a prevalence of maternal anemia to be 41.6% in Delta State, Nigeria. Rouamba et al (2021) Ilorin and Olukosi and Afolabi (2018) in their study in Lagos, Nigeria had higher results of 81.4% prevalence of anaemia. According to Desai et al (2007) and McClure et al (2014), malaria infection is highly associated with anaemia and poor pregnancy outcome at all levels of pregnancy.…”
Section: Discussionmentioning
confidence: 72%
See 1 more Smart Citation
“…The prognosis of COVID-19 and malaria co-infection is also a major cause for concern, particularly in vulnerable malaria populations such as in children and pregnant women with malaria-associated anaemia(M Afolabi and Olukosi, 2018;Oladeinde et al, 2012). Their already compromised immunity raises concerns regarding the effect of co-infection with COVID-19.…”
Section: Covid-19 and Malariamentioning
confidence: 99%
“…Pregnant women are more vulnerable than non-pregnant women to growing problems, such as pulmonary edema, acute respiratory distress syndrome, and hypoglycemia (6)(7)(8). Around 30 million pregnant African women are in danger of malaria infection, whereas 56 million suffer from anemia (9,10). P. falciparum is the most common cause of severe clinical manifestations among the other malaria species, leading to maternal anemia, low birth weight, and pre-term birth.…”
Section: Introductionmentioning
confidence: 99%